Relationship of immunogenetic and immunologic markers and their influence on disease activity and radiological progression in patients with early rheumatoid arthritis - N V Demidova (Научно-практическая ревматология, 2009)
Relationship of immunogenetic and immunologic markers and their influence on disease activity and radiological progression in patients with early rheumatoid arthritis. Objective. To study relationship of shared epitope (SE), anti-cyclic citrullinated peptide (ACCP) antibodies and IgM rheumatoid factor (RF) with disease activity and their prognostic significance in pts with early rheumatoid arthritis (RA). Material and methods. 98 pts with early RA (78 female, 20 male, mean age 47,9±13,7 years,mean disease duration 7,4±5,8 years) were included. 67 (68,4%) from them were RF positive 17and 63 (64,3%) – ACCP positive. 1 or 2 SE (SE+/SE- or SE+/SE+) was present in 63(64,3%) pts. SE was absent in 35 (35,7%) pts. 45 (45,9%) pts had ACCP+/SE+ combination.38 (38,7%) pts were SE, ACCP and RF positive. Activity of RA was assessed with DAS28 and functional status – with Russian version of HAQ questionnaire. C-reactive protein (hsCRP) and IgM RF level was evaluated by nephelometric immunoassay (NIA) with automatic analyzer BN-100, Dade Behring, Germany. ACCP2 was measured by NIA with commercial kits “Axis Shield Diagnostics”, Great Britain. Genomic DNA was isolated by salt extraction with sodium chloride. HLA DRB1 gene olygotyping was performed by polymerase chain reaction with kits “HLA-DR-TEX” (manufacturer SIA “DNA-Technology”, Moscow). Results. ACCP level in SE+/SE- and SE+/SE+ pts was significantly higher than in SE-/SE- pts (p=0,004). IgM RF level in SE+/ACCP+ pts significantly differ from the rest: 351,7±535,8IU/l and 67,8±140,7 IU/l respectively (p<0,001, Mann-Whitney test). After one year of follow up disease activity (DAS28) was significantly higher in SE positive pts, in homozygotes (p=0,017). At baseline radiological examination erosive arthritis was present in 25 (25,5%) pts with early RA. After 12 months erosions were revealed in 48 (48,97%) pts. Erosive changes in SE+/ACCP+ pts did not differ from the rest pts at baseline and after one year of follow up (p=0,08). Conclusion. Presence of SE is associated with high ACCP level, particularly in homozygotes. In SE+/ACCP+ pts IgM RF level was significantly higher. After one year of follow up high inflammatory activity was maintained in SE positive pts. Erosive changes progressed in 23,47% of pts during one year of follow up. SE+ and SE+/ACCP+ pts showed a tendency to faster progression (new erosions appeared almost twice more frequently).